Tren Glamping dalam Berbagai Perspektif sebagai Aktivitas Pariwisata Berbasis Alam: Sebuah Kajian Literatur - Ghaziana Zhafarini; Kurniawan Saefullah; Yunus Winoto (Yayasan Literasi Sains Indonesia, 2025)
Glamping has emerged as a unique accommodation option that offers an exceptional experience in natural environments, attracting particular attention, especially post-pandemic. Its distinction from traditional camping, along with the luxurious facilities it offers, makes glamping an attractive choice for tourists. As part of nature-based tourism, glamping needs to be examined from both sustainability and business perspectives. This paper presents a literature review using a systematic literature review approach. Empirical articles discussing nature-based tourism, specifically glamping, published between 2013 and 2023 were sourced from the reputable ScienceDirect journal portal, yielding 77 articles. These articles were narrowed down to 17 English-language articles that focus on nature-based tourism and glamping as their main topics. This literature review aims to identify research findings related to glamping and its connection to nature-based tourism that have been previously conducted. The study finds several pieces of research indicating that glamping has had a significant impact on tourism post-pandemic and contributes to individual and group development. Other findings discuss how managers are encouraged to actively manage glamping accommodations according to ecological principles while competing in the market by offering facilities that enhance visitor satisfaction and attract investor attention. Recommendations for future research directions include conducting studies that analyze and identify visitor expectations, perceptions, and recommendations through glamping experiences.